TRANSNATIONAL TV EXPOSURE BEHAVIOUR OF LAO AMERICAN WOMEN - Kwanjai, Mesirin (PEOPLE: International Journal of Social Sciences, 2019)
This research explores transnational television, especially exposure to Thai soap operas, and the behaviour of Lao American women nowadays, for remembering their homeland and reminding them of the ethnic and cultural identity of Laos. Questionnaires and interviews were used to collect data in Minnesota, United States, where Thai television soap operas are on a wave of popularity. This research shows that the majority of middle-aged Lao American female audiences habitually watch Thai television programmes, including soap operas, for two to three hours every day via the Thai Global Network satellite channel or websites on the Internet. Thai television viewing considered as a cultural practice becomes the daily routine in the living room between 6 and 10 p.m. Drawing on transnational audiences and uses and gratifications communication theory, the study concludes that the television exposure behaviours of Lao American women as transnational audiences partly connect their memories of their homeland with the pleasures of viewing soaps, while at the same time reflecting the current lack of socioeconomic citizenship status amongst Lao American women due to their poverty, labouring jobs and the inequality of gender roles in family life.